The role of physiotherapists in fall prevention among the elderly: A narrative review (Research, Society and Development, 2025)
Falls are considered high-risk factors for elderly health, potentially leading to long periods of hospitalization, fractures, prolonged immobilization, increased cases of anxiety and depression, and the physiotherapist plays a role in preventing these adverse effects when they occur, as well as guiding family members and institutions that care for these individuals regarding their prevention. The aim of this study is to explain the role of the physiotherapist in fall prevention among the elderly, highlighting intervention strategies focused on maintaining functionality, promoting autonomy, and reducing risks associated with physiological changes due to aging. This is a literature review of a descriptive and qualitative nature, based on articles published between 2020 and 2025, consulted in national and international databases such as SciELO, PubMed, LILACS, and Google Scholar. For the inclusion criteria, 30 publications were selected when applied, the inclusion criteria remained 23 for the formulation of this article, presenting scientific relevance and articles that directly addressed the theme of fall prevention in older adults. The analysis of the studies showed that physiotherapy is central to fall prevention through functional assessment, prescription of individualized exercises, strength training, balance and motor coordination, in addition to the use of established protocols such as the Otago Protocol. Integration with environmental adaptations, health education, and multidisciplinary action enhances the results. It is concluded that physiotherapeutic intervention is essential to preserve the independence, functionality, and quality of life of older adults.